2021
DOI: 10.1093/europace/euab092
|View full text |Cite
|
Sign up to set email alerts
|

The Atrial Fibrillation Better Care pathway for managing atrial fibrillation: a review

Abstract: The 2020 European Society of Cardiology guidelines endorse the Atrial Fibrillation Better Care (ABC) pathway as a structured approach for the management of atrial fibrillation (AF), addressing three principal elements: ‘A’ – avoid stroke (with oral anticoagulation), ‘B’ – patient-focused better symptom management, and ‘C’ – cardiovascular and comorbidity risk factor reduction and management. This review summarizes the definitions used for the ABC criteria in different studies and the impact of adherence/non-ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…Previous studies have shown that therapies compliant with the holistic care (ABC compliance group) were associated with a significantly lower all-cause death and the composite outcome consisting of cardiovascular motality, myocardial infarction, ischemic stroke, total hospitalizations and major bleeding, compared with non-ABC compliant group ( 7 12 ). Also, a system review and a meta-analysis have revealed an obvious risk reduction in ABC group despite the variation including population selection, definition of ABC and clinical outcomes among these studies ( 20 , 21 ). Our findings are consistent with the foregoing studies presenting lower hazard of all-cause death and the composite outcome in patients compliant with ABC care in comparsion to those without ABC pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that therapies compliant with the holistic care (ABC compliance group) were associated with a significantly lower all-cause death and the composite outcome consisting of cardiovascular motality, myocardial infarction, ischemic stroke, total hospitalizations and major bleeding, compared with non-ABC compliant group ( 7 12 ). Also, a system review and a meta-analysis have revealed an obvious risk reduction in ABC group despite the variation including population selection, definition of ABC and clinical outcomes among these studies ( 20 , 21 ). Our findings are consistent with the foregoing studies presenting lower hazard of all-cause death and the composite outcome in patients compliant with ABC care in comparsion to those without ABC pathway.…”
Section: Discussionmentioning
confidence: 99%
“… 51 It leads to improved treatment adherence, reduced perceived treatment burden and better outcomes. 51 , 114 , 115 …”
Section: Integrated Management Of Atrial Fibrillation Patients and Th...mentioning
confidence: 99%
“…The practice of integrated care therefore involves a multidisciplinary team and a close collaboration between different healthcare services across primary, secondary, and tertiary care settings. 51 , 114 , 115 …”
Section: Integrated Management Of Atrial Fibrillation Patients and Th...mentioning
confidence: 99%
See 2 more Smart Citations